Carbamazepine-Induced Nonepileptic Myoclonus in a Child with Autism and Epilepsy - Kirik, Serkan; Yis, Uluc (Georg Thieme Verlag Kg, 2021)
This study deals with a child with different type of seizures several times in week and unresponsive to antiepileptic drugs. Distinguishing between epileptic seizure and motor tic in a patient diagnosed with epilepsy and autism can be challenging. In this study we present a boy on carbamazepine (CBZ) therapy. In the first days of treatment seizure frequency decreased, but after CBZ treatment dosage reached 15mg/kg/day (at the 25th day of the treatment), he presented to the clinic describing several episodes of myoclonus. There were no changes in electroencephalography during the myoclonus. In follow-up, myoclonus was not described after the cessation of CBZ.
Keywords: myoclonus; carbamazepine; child